IDNLearn.com offers a comprehensive solution for finding accurate answers quickly. Ask any question and receive comprehensive, well-informed responses from our dedicated team of experts.

Solve: [tex]-\frac{2}{5}(n+2)=6[/tex]

A. [tex]n=-13[/tex]
B. [tex]n=-10[/tex]
C. [tex]n=17[/tex]
D. [tex]n=-17[/tex]


Sagot :

Certainly! Let's solve the equation step-by-step.

We start with the given equation:
[tex]\[ -\frac{2}{5}(n + 2) = 6 \][/tex]

### Step 1: Isolate the expression containing [tex]\( n \)[/tex]

First, we need to eliminate the fraction by multiplying both sides of the equation by the reciprocal of [tex]\(-\frac{2}{5}\)[/tex], which is [tex]\(-\frac{5}{2}\)[/tex]:

[tex]\[ \left(-\frac{5}{2}\right) \times \left( -\frac{2}{5}(n + 2) \right) = 6 \times \left(-\frac{5}{2}\right) \][/tex]

Simplifying the left-hand side:

[tex]\[ (n + 2) = 6 \times \left(-\frac{5}{2}\right) \][/tex]

### Step 2: Simplify the right-hand side

Calculate the multiplication on the right-hand side:

[tex]\[ 6 \times \left(-\frac{5}{2}\right) = -15 \][/tex]

So the equation now becomes:

[tex]\[ n + 2 = -15 \][/tex]

### Step 3: Solve for [tex]\( n \)[/tex]

To isolate [tex]\( n \)[/tex], subtract 2 from both sides:

[tex]\[ n + 2 - 2 = -15 - 2 \][/tex]

[tex]\[ n = -17 \][/tex]

So, the solution to the equation [tex]\( -\frac{2}{5}(n + 2) = 6 \)[/tex] is:
[tex]\[ n = -17 \][/tex]

### Conclusion

Thus, the correct answer is:
[tex]\[ \boxed{-17} \][/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Find clear and concise answers at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.